Professionals' Tax Liability Assessments and Ethical Evaluations in an Equitable Relief Innocent Spouse Case - Fleischman, Gary (Journal of business ethics, 2003)
This study used a national sample of professionals and a questionnaire containing equitable relief vignettes to explore whether the new equitable relief subset of the revised innocent spouse rules is helpful to the IRS when making relief decisions. The study also addressed the ethical and gender issues associated with equitable relief innocent spouse cases. The results suggested that several equitable relief factors are useful as discriminators in the relief decision. The results also demonstrated that the recognition of an ethical issue and perceptions of moral intensity affected the decision to grant relief in innocent spouse situations. Finally, women subjects were more ethical and more sympathetic toward the victim in an innocent spouse situation than were their male counterparts. These findings have numerous personal and societal implications for businesses, IRS agents, CPAs, and attorneys, as well as other nations wishing to reform their tax structures while assessing the tradeoff between equity and tax revenue generation.